Teacher quality in the twenty first century: new lives, old truths - Day, Christopher (Springer, 2013)
This chapter is based upon a keynote address to the first global teacher education summit, organised by Beijing Normal University in 2011, in which research across the world about influences which affect teachers' sense of professional identity, capacity for compassion, commitment, resilience and effectiveness long after they have graduated from their pre-service education and training programmes in universities and colleges were shared. The findings suggest that teaching pre-service students about how the conditions in which they work may enhance or diminish their capacity to teach to their best and how they might act to mediate these is a key part of the work of all teacher educators and an important focus for the work of educational researchers.